TRENDS IN USE OF RAPID DIAGNOSTIC TESTS - E.Georgieva; N. Ermenlieva; S. Stamova; K. Varlyakov; P. Teneva (Trakia Journal of Sciences)
INTRODUCTION: Laboratory diagnostics worldwide is changing daily. Digitizing it by introducing sensors and new rapid diagnostic tests plays an important role in protecting public health. There is still a lack of widespread use of these types of sensors and tests in Bulgaria. The aim of this study was to establish the level of awareness and frequency of use of rapid tests. MATERIALS: The study used a documentary method comprising a systematic review of scientific publications from medical journals published in electronicdatabases such as PubMed, Scopus, Web of Science, etc. in the studied field.Sociological methods were used by anonymous survey among 980 respondents to explorethe opinion of users of rapid tests and sensors for laboratory parameters. The study covers the period October 2018 -February 2019 and November -December 2024. MS Office Excel package and ANOVA statistical method were used for data processing.RESULTS: We investigatedthe use of rapid tests and devices for determination of laboratory indices, andfound that the predominant users of monthly tests were 73.5%, only 1-2 times a year occupyinga relative share of 16.3%, and the users who self-tested weekly were 10.2%.The survey data showed the largest difference in the use of rapid tests for influenza(2018-2019 3.20%/2024 jumped to 25%) and COVID (2018-2019 3.20%/2024 jumped to 32%) followed by tests used for glucose testing and glucometer and sensor supplies. Pregnancy test use also increased to 23.3%, other tests roughly maintained their use over the studied period. CONCLUSION: Globally, the consumption of sensors and rapid diagnostic tests is a growing trend due to the dynamics of viral diseases, aging population and centralization of healthcare. The use of rapid diagnostic tests in Bulgaria is projected to continue to increase, especially in the context of greater availability of technology and in response to pandemic or epidemic threats. Rapid diagnostics are expected to become more prevalent not only in hospitals and healthcare settings, but also in other public and corporate spheres as part of efforts to prevent the spread of disease and improve public health.